Adsorption and desorption kinetic studies of bioactive phenolics purification on selected macroporous resins - Mohamed Idris, Zulkarnain; Rostam, Nur Farahin; Mohamed Dzahir, Mohd Irfan Hatim; Jamal, Parveen; Ahmad Barkat, Anumsima (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
In this study, two different types of macroporous resins known as XAD-7HP and HP-20 were evaluated for the adsorption and desorption properties against bioactive phenolics extracted from Phanerochaete chrysosporium. The study was conducted at different phase contact time, solution pH and ethanol concentration by static adsorption and desorption methods. From the results, it was found that the adsorption capacity for both resins has no significant difference. Meanwhile in desorption study, HP-20 and XAD-7HP gave 90.52% and 88.28% recoveries, respectively. Then, the kinetic adsorption data were analyzed with both pseudo-first-order and pseudo-second-order equations and the later performed better. The adsorption isotherm data were fitted well by both Langmuir and Freundlich models.